Time perception mechanisms at central nervous system - Rhailana Fontes; Jéssica Ribeiro; Daya S. Gupta; Dionis Machado; Fernando Lopes-Júnior; Francisco Magalhães; Victor Hugo Bastos; Kaline Rocha; Victor Marinho; Gildário Lima; Bruna Velasques; Pedro Ribeiro; et al. (MDPI AG, 2016)
The five senses have specific ways to receive environmental information and lead to central nervous system. The perception of time is the sum of stimuli associated with cognitive processes and environmental changes. Thus, the perception of time requires a complex neural mechanism and may be changed by emotional state, level of attention, memory and diseases. Despite this knowledge, the neural mechanisms of time perception are not yet fully understood. The objective is to relate the mechanisms involved the neurofunctional aspects, theories, executive functions and pathologies that contribute the understanding of temporal perception. Articles form 1980 to 2015 were searched by using the key themes: neuroanatomy, neurophysiology, theories, time cells, memory, schizophrenia, depression, attention-deficit hyperactivity disorder and Parkinson's disease combined with the term perception of time. We evaluated 158 articles within the inclusion criteria for the purpose of the study. We conclude that research about the holdings of the frontal cortex, parietal, basal ganglia, cerebellum and hippocampus have provided advances in the understanding of the regions related to the perception of time. In neurological and psychiatric disorders, the understanding of time depends on the severity of the diseases and the type of tasks.